DEVELOPMENT OF A MODEL FOR THE PROTECTION OF PERSONAL DATA IN SOCIAL NETWORKS - Laptiev, Serhii (Ukrainian Information Security Research Journal, 2024)
Tens of millions of people around the world become victims of identity theft every year. Netizens lose huge amounts of money due to fraudsters who use their data in an illegal way, and absolutely anyone can become a victim. Identity theft is any crime in which an attacker obtains another person’s data and uses the victim’s identity to commit fraud. According to research, data theft caused 16 billion in losses to 15.4 million consumers in the United States in 2020. In the same year, the British fraud prevention organization Cifas recorded almost 173,000 cases of identity fraud in the UK. This is the largest number of fraud cases in the last 13 years. Therefore, the problem of developing and researching mathematical models of personal data protection is very relevant. The work is devoted to solving the task of developing a model and researching the stability of the personal information protection system. Monitoring the behavior of the dynamic information protection system is an important direction. The paper analyzed the behavior of the information protection system using the methods of the qualitative theory of differential equations, in particular the phase plane method. With the help of this method, the characteristics of special points, isolated closed trajectories and separatrices are found, which in turn allows to evaluate the dynamics of the studied nonlinear dynamic system in a wide range of possible initial conditions. The phase plane illustrates the full variety of possible states of the system, and describes the picture of its dynamics. The paper presents simulation results that prove the adequacy of the developed model. It is confirmed that the developed model of personal data protection is stable, taking into account the attack termination time and the assigned modeling parameters. Using the phase plane method is a new method for researching the stability of the information protection model.